Multiplexing of TMT labeling reveals folate-deficient diet-specific proteome changes in NTDs - Pei, Pei; Shen, Jinying; He, Xuejia; Zeng, Yubing; Zhang, Ting; Wang, Shan (Frontiers in Cell and Developmental Biology, 2024)
Background: In the early stage of embryonic development, the neural tube (NT) cannot be closed properly due to some complex factors such as, environmental factors, genetic factors and the relationship between various factors, leading to the occurrence of neural tube defects (NTDs). Methods: In this study, we induced a mouse model of NTDs by feeding mice with low-folate diet and intraperitoneally injected with 1.5mg/kg methotrexate on E7.5. Fetal mice were achieved at E13.5, then we extracted proteins from brain tissues with trypsin digestion. After enzymatic digestion, peptides were labeled with TMT/iTRAQ and then separated in high-performance liquid chromatography (HPLC) for subsequent LC-MS/MS analysis. To analyze the functional enrichment of differentially expressed proteins(DEPs) in the NTDs mice tissues with low folate induction, we used Gene Ontology(GO) and Kyoto Encyclopedia of Genes and Genomes(KEGG) pathway annotation to analyze proteomic changes. Results: Low folate induced mouse model was successfully constructed. Folate was used as a sensitizing agent, the teratogenicity rate of the NTDs fetal mice was increased to 36.5% when the concentration of methotrexate was at 1.5mg/kg.. 6614 proteins were identified by mass spectrometry, among them, 5656 proteins were quantified. In the following proteomic analysis, GO classification and KEGG pathway enrichment analysis were conducted, and heatmaps were drawn for differentially expressed proteins(DEPs). Moreover, the main pathways associated with NTDs, such as Hedgehog, Wnt, p53, Hippo signaling pathways, and one carbon pool by folate, can be identified through protein-protein interaction (PPI) network. It was also found that the regulation of ribosomal proteins has a certain impact on neural tube development, such as RPL13 and RPL14, which are upregulated in NTDs. Conclusions: Our results revealed proteomic changes in the tissues of low folate induced NTDs mice, validation showed that ribosomal proteins play a regulatory role during the development of NTDs, it provides new ideas for the pathogenesis and preventive measures of NTDs.